2011
DOI: 10.1002/chem.201003156
|View full text |Cite
|
Sign up to set email alerts
|

Evolution from Lyotropic Liquid Crystal to Helical Fibrous Organogel of an Achiral Fluorescent Twin‐Tapered Bi‐1,3,4‐oxadiazole Derivative

Abstract: We report an unprecedented hierarchical self-assembly of an achiral twin-tapered bi-1,3,4-oxadiazole derivative (2,2-bis(3,4,5-trioctanoxyphenyl)-bi-1,3,4-oxadiazole, BOXD-T8). This molecule can form a layer-structured lyotropic liquid crystal and further forms a helical fibrous organogel in DMF at concentrations above 0.6 wt %. The self-assembly process of BOXD-T8 in DMF is accompanied by a change in its fluorescence. The pitches of the helical fibers are non-uniform, and both left- and right-handed helical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…31 In our previous work, we reported a bi-1,3,4-oxadiazole derivative (BOXD-T8) (Scheme 1), which showed intermolecular charge transition at certain concentration range. 32,33 Our present work demonstrated that the energy transfer may be involved in BOXD-T8-SWNTs and BOXD-T8-GO composites in solution. It was demonstrated that BOXD-T8/CNM organogels showed reinforced aggregation.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…31 In our previous work, we reported a bi-1,3,4-oxadiazole derivative (BOXD-T8) (Scheme 1), which showed intermolecular charge transition at certain concentration range. 32,33 Our present work demonstrated that the energy transfer may be involved in BOXD-T8-SWNTs and BOXD-T8-GO composites in solution. It was demonstrated that BOXD-T8/CNM organogels showed reinforced aggregation.…”
Section: Introductionmentioning
confidence: 51%
“…The gelator BOXD-T8 was synthesized according to the literature methods. 32 Its structure was characterized by FT-IR, 1 H NMR spectroscopy and elemental analysis (see ESI †). SWNTs were purchased from Shenzhen Nanotech Port Co., Ltd, having an outer diameter of 10-20 nm and length of o2 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The hierarchical self-assembly process was accompanied by a change in its uorescence, which was attributed to the intermolecular p-p interactions between aromatic segments. 91 Notably, compound 51 could emit strong uorescence and amplied spontaneous emission (ASE) both in solution and in an aligned ordered solid state, which made it potentially useful in preparing functional supramolecular architectures with ultralow-threshold ASE. 92 In 2010, Gallardo et al 93 synthesized a D 4h -symmetric discotic liquid crystalline 1,3,4-oxadiazole 52 (Scheme 28) with an azo linkage in the core of the molecule.…”
Section: Disk-like Liquid Crystalsmentioning
confidence: 99%
“…18 and 19). 89 The formation of such a supramolecular structure is dependent on the solvent and concentration. It is considered that the intermolecular p-p interactions between aromatic segments are the main driving forces for the formation of brous nanomaterials, while the weak van der Waals forces between alkyl chains are the cause of the helical ne structures of the bers made of achiral 17.…”
Section: Organogels With Conventional Chromophoresmentioning
confidence: 99%